2021
DOI: 10.1039/d1ob01733k
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-catalyzed intramolecular cyclopropanation of alkenes with α-bromo-β-keto esters

Abstract: Mild photoredox-catalyzed intramolecular cyclopropanation of alkenes with α-bromo-β-keto esters in an aqueous medium was developed. The sequential reaction process comprising intramolecular radical addition of α-bromo-β-keto esters to olefins under photoredox...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…There is one brief mention of its use in a cyclopropanation, [27] mediated by indium; however, this is quite an esoteric single reaction example. Several related compounds (BrCXYCO 2 R, where X=an electron withdrawing group and Y=an electron withdrawing group or H) have been used in cyclopropanations [28a–d] or in generation of a radical by photocatalysis for use in addition reactions [28e–g] . We found that it was possible to directly swap the CH 2 I 2 for ethyl dibromoacetate and that its use led to the formation of the desired products 4 with good to high yields (65–80 %, Scheme 5).…”
Section: Resultsmentioning
confidence: 93%
“…There is one brief mention of its use in a cyclopropanation, [27] mediated by indium; however, this is quite an esoteric single reaction example. Several related compounds (BrCXYCO 2 R, where X=an electron withdrawing group and Y=an electron withdrawing group or H) have been used in cyclopropanations [28a–d] or in generation of a radical by photocatalysis for use in addition reactions [28e–g] . We found that it was possible to directly swap the CH 2 I 2 for ethyl dibromoacetate and that its use led to the formation of the desired products 4 with good to high yields (65–80 %, Scheme 5).…”
Section: Resultsmentioning
confidence: 93%
“…When the monomers PTH-M1 and PTH-M2 were used instead, the reactions delivered higher yields (entries 3–4, Table ). Interestingly, bromoalkylation and cyclopropanation products were produced simultaneously. Furthermore, significantly improved conversion was achieved by employing porous materials PTH-POP1 and PTH-POP2 as the catalysts, suggesting polymerization brought enhanced reactivity. Consistent with the more favorable optical and electronic properties (Figure ), PTH-POP2 gave higher yields of the mixture compared with that of PTH-POP1 (entries 5–6, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Carreira and co-workers ( 39 ) recently reported a photoredox benzothiazinoquinoxaline–catalyzed cyclopropanation of alkenes with α-bromo-β-ketoesters and α-bromomalonates through a radical ATRA followed by a base-promoted intramolecular 1,3-S N 2 process. Tokuyama and co-workers ( 48 ) reported a photocatalytic intramolecular cyclopropanation of α-bromodicarbonyls with a pendant alkene, which proceeded by an ATRA/1,3-S N 2 sequence. Molander and co-workers ( 27 ) observed a radical polar crossover mechanism in photoredox alkene cyclopropanation with an iodomethylsilicate.…”
Section: Mechanistic Studiesmentioning
confidence: 99%